The Effect of Journalist Questions on Students’ Writing Recount Text (RETAIN, 2018)
AbstractThis study aimed to find out the effect of journalist questions on students’ ability in writing recount text. This research was carried out on experimental and control groups. The participants were the tenth graders of SMKN 1 Jombang. A pre-test was given to both groups before the treatment to find out the writing performance of the participants. During the study, experimental group was taught through journalist questions meanwhile control group was taught through conventional method. An independent samples t-test was used to know whether there was a significant difference or not between experimental and control groups. The results gotten from the post-test showed that there was a significant difference between those two groups which signifies that journalist questions had a significant effect on tenth graders’ ability in writing recount text. The participants in experimental groups were also demonstrated questionnaire to elicit their opinion about the effectiveness of using journalist questions in writing recount text. The result showed that the tenth graders have a positive response towards the use of journalist questions in writing recount text.Key words : Journalist Question, writing, recount text.AbstrakPenelitian ini bertujuan untuk mengetahui pengaruh pertanyaan jurnalistik terhadap kemampuan siswa dalam menulis teks recount. Penelitian ini dilakukan pada dua kelompok, yakni kelompok eksperimen dan kontrol. Para siswa adalah siswa kelas X di SMKN 1 Jombang. Sebelum melakukan treatmen, pre-tes diberikan kepada kedua kelompok untuk menyelidiki kinerja menulis dari peserta didik. Sepanjang penelitian, kelompok eksperimen diajarkan melalui pertanyaan jurnalistik sedangkan kelompok kontrol diajarkan melalui metode konvensional. Sebuah uji t-test sampel independen diterapkan untuk mengetahui apakah ada perbedaan yang signifikan secara statistik atau tidak antara kedua kelompok. Hasil yang diperoleh dari post-tes menunjukkan bahwa terdapat perbedaan signifikan antara kelompok eksperimen dan kontrol, yang menandakan bahwa pertanyaan jurnalistik memiliki pengaruh signifikan terhadap kemampuan siswa dalam menulis teks recount. Setelah treatmen, kelompok eksperimen juga menunjukkan kuesioner untuk mendapatkan pendapat merekaa tentang efektivitas menggunakan pertanyaan jurnalistik dalam menulis teks recount. Hasil dari penelitian ini menunjukkan bahwa siswa kelas X memiliki respon positif terhadap penggunaan pertanyaan jurnalistik dalam menulis teks recount.Kata Kunci: Petranyaan jurnalistik, menulis, teks recount